Characteristics of rhizosphere and bulk soil microbial community of Chinese cabbage (Brassica campestris) grown in Karst area - Wei, Xiaoliao; Fu, Tianling; He, Guandi; Zhong, Zhuoyan; Yang, Mingfang; Lou, Fei; He, Tengbing (Frontiers in Microbiology, 2023)
Understanding the rhizosphere soil microbial community and its relationship to the bulk soil microbial community is critical for maintaining soil health and fertility, and improving crop yields in Karst regions. The microbial communities in the rhizosphere and bulk soil of a Chinese cabbage (Brassica campestris) plantation in a Karst region, as well as their relationships with soil nutrients, were examined in this work using high-throughput sequencing technologies of 16S and ITS amplicons. The aim was to provide theoretical insights into the healthy cultivation of Chinese cabbage in a Karst area. The findings revealed that the rhizosphere soil showed higher contents of organic matter (OM), alkaline hydrolyzable nitrogen (AN), available phosphorus (AP), total phosphorus (TP), available potassium (AK), total potassium (TK), total nitrogen (TN), catalase (CA), urease (UR), sucrase (SU), and phosphatase (PHO) comparison to bulk soil; while the pH value showed the opposite trend. The diversity of bacterial and fungal communities in the bulk soil was higher than that in the rhizosphere soil, and their compositions differed between the two types of soil. In the rhizosphere soil, Proteobacteria, Acidobacteriota, Actinobacteriota, and Bacteroidota were the dominant bacterial phyla, while Olpidiomycota, Ascomycota, Mortierellomycota, and Basidiomycota were the predominant fungal phyla. In contrast, the bulk soil, was characterized by bacterial dominance of Proteobacteria, Acidobacteriota, Chloroflexi, and Actinobacteriota and fungal dominance of Ascomycota, Olpidiomycota, Mortierellomycota, and Basidiomycota. The fungal network was simpler than the bacterial network, and both networks exhibited less complexity in the rhizosphere soil compared to the bulk soil. Moreover, the rhizosphere soil harbored a higher proportion of beneficial Rhizobiales. The rhizosphere soil network was less complicated than the network in bulk soil by building a bacterial-fungal co-occurrence network. Furthermore, a network of relationships between soil properties and network keystone taxa, revealing that the rhizosphere soil keystone taxa were more strongly correlated with soil properties than those in the bulk soil, despite its lower complexity, the rhizosphere soil contains a higher abundance of bacteria beneficial for cabbage growth compared to the bulk soil.